SIFAT KIMIA TANAH, PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) YANG DIBERI KASCING DAN ZAT PENGATUR TUMBUH PADA SPODOSOL: The Chemical Properties, growth an yield of Meloon (Cucumis melo L.) Which given vermicompost and growth Regulatory Substances on Spodosol - Sih Winarti; Basuki Basuki; Sri Endang Agustina Rahayuningsih; Panjaitan A. R; Sinarmata T. J. (AgriPeat, 2022)
This study aims to determine the effect of vermicompost fertilizer on changes in the chemical properties of spodosol as a growing medium for melons and to determine the growth and yield of melons treated with gibberellins as growth regulators. The study used a Factorial Completely Randomized Design. The first factor is the dose of vermicompost 0, 60, 90, 120 and 150 g vermicompost per polybag equivalent to 0, 10, 15, 20 and 25 t. vermicompost ha-1. The second factor is the provision of plant growth regulators Agrogibb 40 SL given in the generative phase consisting of 2 two levels, namely: 0 and 0.5 mL L-1 with 4 replications. The results showed that the application of vermicompost fertilizer on spodosols was able to increase soil pH and available P, but organic C and total soil N tended to decrease, plants were able to grow significantly better. There was no interaction between the application of vermicompost fertilizer and plant growth regulators giberelin on the yield of melons. Kascing fertilizer with a dose of 90 g plant-1, the fruit flesh was thicker and the highest tight weight was obtained at a dose of 120 g plant-1. The application of gibberellin growth regulator with a concentration of 0.5 mL L-1 was able to significantly increase fruit weight, fruit diameter, fruit thickness, wet and dry weight of melon plants